2019
DOI: 10.1113/ep088028
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen inhalation attenuated bleomycin‐induced pulmonary fibrosis by inhibiting transforming growth factor‐β1 and relevant oxidative stress and epithelial‐to‐mesenchymal transition

Abstract: New Findings What is the central question of this study?The aim was to explore the effects and underlying mechanisms of H2 on bleomycin‐induced pulmonary fibrosis. What are the main findings and its importance?Our results indicate that, in bleomycin‐induced pulmonary fibrosis, H2 inhalation attenuated oxidative stress and reversed the pulmonary epithelial‐to‐mesenchymal transition process by reducing reactive oxygen species production and inhibiting the expression of transforming growth factor‐β1, α‐smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…It is believed that it has biological effects such as anti‐oxidation, anti‐inflammation, and anti‐apoptosis, and has extremely high biosafety. Hydrogen has already been reported to protect kidney, liver, heart, and lung from fibrosis . Studies have also suggested that peritoneal dialysate containing hydrogen could preserve MCs, indicating hydrogen may suppress peritoneal fibrosis .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is believed that it has biological effects such as anti‐oxidation, anti‐inflammation, and anti‐apoptosis, and has extremely high biosafety. Hydrogen has already been reported to protect kidney, liver, heart, and lung from fibrosis . Studies have also suggested that peritoneal dialysate containing hydrogen could preserve MCs, indicating hydrogen may suppress peritoneal fibrosis .…”
Section: Introductionmentioning
confidence: 95%
“…Hydrogen has already been reported to protect kidney, liver, heart, and lung from fibrosis. [16][17][18][19] Studies have also suggested that peritoneal dialysate containing hydrogen could preserve MCs, indicating hydrogen may suppress peritoneal fibrosis. 20 A clinical case report has indicated that hydrogen-dissolved peritoneal dialysate could successfully treat a patient with encapsulating peritoneal sclerosis.…”
mentioning
confidence: 99%
“…A previous study using a bleomycin-induced ALI model was reported by Gao and colleagues who found that hydrogen attenuated oxidative stress, increased the expression of the antioxidant glutathione peroxidase, and consequently suppressed the expression of reactive oxygen species in the injured lung [13]. The expression of TGF-β1 was also suppressed and epithelial-to-mesenchymal transition was inhibited, which may be one mechanisms involved in brosis suppression by hydrogen treatment.…”
Section: Discussionmentioning
confidence: 76%
“…Inhalation of hydrogen gas may be a straightforward and promising therapeutic option, because inhaled gaseous molecules can directly reach the alveoli. Additionally, inhaled hydrogen has a low chemical toxicity [11][12][13]. Thus, this gaseous therapy has good clinical feasibility, as long as its ammability can be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Bleomycin intercalates into DNA, causing single-and double-strand breaks, thereby arresting cell division and DNA synthesis. Its properties have been exploited to treat some cancers [38][39][40]. Luna et al [41] used the BLM assay to identify chromosomal damage in fertile and sub-fertile female cows.…”
Section: Plos Onementioning
confidence: 99%